Phosphorylation-Mediated Dynamics of Nitrate Transceptor NRT1.1 Regulate Auxin Flux and Nitrate Signaling in Lateral Root Growth - Zhang, Xi; Cui, Yaning; Yu, Meng; Su, Bodan; Gong, Wei; Baluška, František; Komis, George; Šamaj, Jozef; Shan, Xiaoyi; Lin, Jinxing (Plant physiology, 2019)
The dual-affinity nitrate transceptor NITRATE TRANSPORTER1.1 (NRT1.1) has two modes of transport and signaling, governed by Thr-101 (T101) phosphorylation. NRT1.1 regulates lateral root (LR) development by modulating nitrate-dependent basipetal auxin export and nitrate-mediated signal transduction. Here, using the Arabidopsis (Arabidopsis thaliana) NRT1.1T101D phosphomimetic and NRT1.1T101A nonphosphorylatable mutants, we found that the phosphorylation state of NRT1.1 plays a key role in NRT1.1 function during LR development. Single-particle tracking revealed that phosphorylation affected NRT1.1 spatiotemporal dynamics. The phosphomimetic NRT1.1T101D form showed fast lateral mobility and membrane partitioning that facilitated auxin flux under low-nitrate conditions. By contrast, nonphosphorylatable NRT1.1T101A showed low lateral mobility and oligomerized at the plasma membrane (PM), where it induced endocytosis via the clathrin-mediated endocytosis and microdomain-mediated endocytosis pathways under high-nitrate conditions. These behaviors promoted LR development by suppressing NRT1.1-controlled auxin transport on the PM and stimulating Ca2+-ARABIDOPSIS NITRATE REGULATED1 signaling from the endosome.
Keywords: proteiny huseníčku; Calcium Signaling; kořeny rostlin; Anion Transport Proteins; fosforylace; Plant Roots; Arabidopsis; Indoleacetic Acids; Plant Proteins; proteiny přenášející anionty; dusičnany; rostlinné proteiny; transkripční faktory; Nitrates; Transcription Factors; Phosphorylation; kyseliny indoloctové; vápníková signalizace; Arabidopsis Proteins